The Elusive Destination Brand and the ATLAS Wheel of Place Brand Management. (January 2021) - Kavaratzis, Mihalis; Hatch, Mary Jo
This conceptual article reconsiders the formation of destination and place brands. It proposes that brands initiate people's meaning making over the place directly involving them in the branding process. Using a combination of process-based approaches to brands and places, the article substantiates the argument that the place brand's quintessence lies in the constant alterations it causes to the meaning of the place as stakeholders interact, thereby keeping the brand active and in constant formation. The distinction between conceived, perceived, and lived dimensions of a place brand is used to conceptualize the brand as open-ended, allowing for different interpretations to occur and different meanings to develop. This makes the brand rather elusive. The article accounts for the implications of the elusiveness of place brands for place brand management and proposes the ATLAS wheel of place brand management as a tool to follow and influence the place brand in its on-going formation.